Philosophy and Synergy of Information: Sustainability and Security - Kervalishvili, Paata J (IOS Press, 2014)
Philosophy of Information is one of the most exciting and fruitful areas of philosophical research of our time. It is already affecting the overall way in which new and old philosophical problems are being addressed, bringing about a substantial innovation of the philosophical system. Information is conveyed by perception, and retained by memory, though also transmitted by means of language. The concept Information is acquired without one's necessarily having a grasp of the proposition which embodies it; the flow of information operates at a much more basic level than the acquisition and transmission of knowledge. This represents the information turn in philosophy.